On Epistemic Appropriation - Davis, Emmalon (Ethics, 2018)
In this article, I offer an account of an unjust epistemic practice―namely, epistemic appropriation―that harms marginalized knowers through the course of conceptual dissemination and intercommunal uptake. The harm of epistemic appropriation is twofold. First, while epistemic resources developed within the margins gain uptake with dominant audiences, those resources are overtly detached from the marginalized knowers responsible for their production. Second, epistemic resources developed within, but detached from, the margins are utilized in dominant discourses in ways that disproportionately benefit the powerful.
Keywords: approches et analyses; appropriation épistémique; cours; cycles supérieurs; discipline; discours dominant; droits des personnes; fem9000; injustices épistémiques; inégalités; philosophie; privilèges; rapports de pouvoir; savoirs des marges; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique

Credibility Excess and the Social Imaginary in Cases of Sexual Assault - Yap, Audrey S (Feminist Philosophy Quarterly, 2017)
This paper will connect literature on epistemic injustice with literature on victims and perpetrators, to argue that in addition to considering the credibility deficit suffered by many victims, we should also consider the credibility excess accorded to many perpetrators. Epistemic injustice, as discussed by Miranda Fricker, considers ways in which someone might be wronged in their capacity as a knower. Testimonial injustice occurs when there is a credibility deficit as a result of identity-prejudicial stereotypes. However, criticisms of Fricker have pointed out that credibility is part of a more complex system that includes both deficits and excesses. I will use these points to argue that we should look closer at sources of credibility excess in cases of sexual assault. This means that in addition to considering sources of victim blaming by looking at ways in which “ideal” victims are constructed, we also need to consider ways in which “ideal” perpetrators are constructed.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; injustices testimoniales; injustices épistémiques; inégalités; philosophie; philosophie féministe; privilèges; racisme; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; éxcès de crédibilité

Epistemic Exploitation - Berenstain, Nora (Ergo, an Open Access Journal of Philosophy, 2016)
Epistemic exploitation occurs when privileged persons compel marginalized persons to educate them about the nature of their oppression. I argue that epistemic exploitation is marked by unrecognized, uncompensated, emotionally taxing, coerced epistemic labor. The coercive and exploitative aspects of the phenomenon are exemplified by the unpaid nature of the educational labor and its associated opportunity costs, the double bind that marginalized persons must navigate when faced with the demand to educate, and the need for additional labor created by the default skepticism of the privileged. I explore the connections between epistemic exploitation and the two varieties of epistemic injustice that Fricker (2007) identifies, testimonial and hermeneutical injustice. I situate epistemic exploitation within Dotson’s (2012; 2014) framework of epistemic oppression, and I address the role that epistemic exploitation plays in maintaining active ignorance and upholding dominant epistemic frameworks.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; discours dominant; exploitation épistémique; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; inégalités; oppression épistémique; philosophie; privilèges; sciences humaines; systèmes d'oppressions; thématiques; travail; violences; éthique

Typecasts, Tokens, and Spokespersons: A Case for Credibility Excess as Testimonial Injustice - Davis, Emmalon (Hypatia, 2016)
Miranda Fricker maintains that testimonial injustice is a matter of credibility deficit, not excess. In this article, I argue that this restricted characterízation of testimonial injustice is too narrow. I introduce a type of identity-prejudicial credibility excess that harms its targets qua knowers and transmitters of knowledge. I show how positive stereotyping and prejudicially inflated credibility assessments contribute to the continued epistemic oppression of marginalized knowers. In particular, I examine harms such as typecasting, compulsory representation, and epistemic exploitation and consider what hearers are obligated to do in response to these injustices. I argue that because epistemic harms to rnarginatized knowers also arise from prejudicially inflated assessments of their credibility, the virtue of testimonial justice must be revised to remedy them.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; droits des personnes; excès de crédibilité; fem9000; fricker; injustices testimoniales; inégalités; justice sociale; philosophie; privilèges; sciences humaines; systèmes d'oppressions; thématiques; violences; éthique